Interstitial Granulomatous Drug Reaction to Ustekinumab - A. Walker; J. S. Westerdahl; J. Zussman; J. Mathis (Case Reports in Dermatological Medicine)
Interstitial granulomatous drug reaction (IGDR) is a distinct inflammatory process that often presents as annular, violaceous plaques distributed on the extremities, proximal trunk, and intertriginous areas. The list of drugs implicated for inciting IGDR is growing, but most prominently includes ACE inhibitors, antihistamines, beta-blockers, antidepressants, and anticonvulsants. Ustekinumab is a human monoclonal antibody that targets inflammatory cytokines IL-12 and IL-23 and has been have shown to be effective in treating IGDR. However, we present a case that suggests ustekinumab can also act as an inciting agent for IGDR.